Relationship between cardiac biomarker concentrations and long-term mortality in subjects with osteoarthritis - Rehm, Martin; Büchele, Gisela; Peter, Raphael Simon; Brenner, Rolf Erwin; Günther, Klaus-Peter; Brenner, Hermann; Koenig, Wolfgang; Rothenbacher, Dietrich (PLOS ONE, 2020)
Osteoarthritis (OA) is associated with adverse cardio-metabolic features. N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity troponins T and I (hs-cTnT and hs-cTnI) are well-characterized cardiac markers and provide prognostic information. The objective was to assess the association of cardiac biomarker concentrations with long-term mortality in subjects with OA. In a cohort of 679 OA subjects, undergoing hip or knee replacement during 1995/1996, cardiac biomarkers were measured and subjects were followed over 20 years. During a median follow-up of 18.4 years, 332 (48.9%) subjects died. Median of hs-cTnT, hs-cTnI, and NT-proBNP at baseline was 3.2 ng/L, 3.9 ng/L, and 96.8 ng/L. The top quartile of NT-proBNP was associated with increased risk of mortality (Hazard Ratio (HR) 1.79, 95% confidence interval (CI) 1.17-2.73) after adjustment for covariates including troponins (hs-cTnT HR 1.30 (95% CI 0.90-1.89), hs-cTnI HR 1.32 (95% CI 0.87-2.00) for top category). When biomarker associations were evaluated as continuous variables, only NT-proBNP (HR per log-unit increment 1.34, 95% CI 1.16-1.54) and hs-cTnI (HR 1.38, 95% CI 1.11-1.72) showed robust results. Elevated cardiac biomarker concentrations predicted an increased risk of long-term mortality and strongest for NT-proBNP and hs-cTnI. These results might help to identify subjects at risk and target preventive efforts early.